Manganese micro-alloyed titanium aluminide alloys fabricated using laser engineering net shaping - Motha, Sibusisiwe (My University, 2022)
This dissertation focuses on the fabrication of Ti-Al-Mn alloys using Laser Engineered Net Shaping (LENS) as a fabrication process. Through the determination of the best combination of LENS parameters, Ti-based alloy microstructures yielding the best combination mechanical properties which include improved ductility and strength, were established. Microstructures and nanostructures were analysed through Scanning Electron Microscopy, Xray Diffraction and Electron Backscatter Diffraction. Mechanical properties were studied by performing microhardness tests, nano indentation, measurement of post process thermal cracks and Gleeble tests. Studies of these structures and mechanical behaviour were connected using literature. Numerical models were established to illustrate the thermodynamics behind using LENS as a fabrication process to produce Ti-based alloys. It was established that high Mn powder feed rates in the production of Ti-Mn alloys led to the production of undesirable Mn0.52Ti0.48(s) phase which is brittle and has high density. However, the production of TiMn using low Mn powder feed rates yielded structures comprised of disorder a-HCP dendrites withina B-BCC matrix with mechanical properties that include improved mechanical strength. However, the addition of Al to TiMn, is detrimental for ductility. Heat treatment procedures led to an increase in dislocation densities and reduced hardness. Low Mn TiMn alloys yield improved fracture stress compared to TiAl and TiAlMn, and can withstand temperatures as high as 130 C. It has also been observed that lower laser power settings led to rapid post processing thermal cracking due to reduced thermal gradients which lead to higher thermal residual stresses during processing which rapidly exceed the fracture toughness. High temperature ductility and mechanical strength of TiAlMn improved simultaneously until a strain value of 34.58%, beyond which yield strength deteriorated. It was also established that ductility and mechanical strength are favoured by dislocation motion. However, beyond the strain value of 34.58%, dislocation densities reduce with reducing yield strength, which further supports the existing imbalance between mechanical strength and ductility in TiAl based alloys
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2022